Pemanfaatan Limbah Plastik PS (Polystyrene) Jenis Styrofoam menjadi Paving Block dengan Campuran Silica Fume sebagai Upaya Reduksi Sampah Plastik: indonesia - Ardiatma, Dodit; Ilyas, Nur Ilman; Halomoan, Nico; Indriyani, Yuyun Mei (Jurnal Sains dan Teknologi Lingkungan, 2025)
As the population increases, the amount of plastic waste, especially styrofoam, is also increasing. Styrofoam waste that is not disposed of and accumulates will have a negative impact on health and the environment. On the other hand, the utilization of styrofoam waste as an additional material for building materials is still very minimal. Therefore, this research aims to overcome environmental problems by utilizing styrofoam waste in making paving blocks as an alternative building material. This research uses a quantitative method to determine the quality of paving blocks produced from a mixture of styrofoam and silica fumes. The research process begins with paving blocks containing 10% styrofoam from the total sand, with variations in particle size that pass the mesh sieve of 1mm, 4mm, and 10mm. Styrofoam acts as a partial replacement for coarse and fine aggregates. In addition, silica fume was added as much as 10% of the total cement to partially replace the adhesive material. The results showed that the addition of styrofoam waste with a diameter of 1mm, 4mm, and 10mm mesh passes in paving blocks produced compressive strength values of 18.00 MPa, 29.17 MPa, and 32.34 MPa, respectively, as well as water absorption values of 6%, 4.9%, and 3.6%. The larger styrofoam shredding diameter (10mm mesh) produced the highest compressive strength value (32.34 MPa) and the lowest water absorption (3.6%), meeting SNI 03-0692-1996 and quality classification B for parking lots. The best composition is the addition of styrofoam by 10% of sand and silica fume by 10% of cement, with 10mm mesh shredding diameter. The styrofoam shredding diameter proved to have a significant effect on increasing the compressive strength and decreasing the water absorption of paving blocks. This research is expected to provide a practical solution in reducing styrofoam waste by using it as a building material, while producing paving block products that meet quality standards.